Pelaksanaan Rekrutmen dan Seleksi Tenaga Pendidik Di SMA Nurul Amal Palembang - Rabial Kanada (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2020)
This study discusses the implementation of the recruitment of educators and the factors that influence the implementation of the recruitment of educators at SMA Nurul Amal Palembang. This study uses a type of research that is qualitative. Methods of data collection using the method of observation, interviews and documentation. Data analysis techniques used are data reduction, data presentation and verification or drawing conclusions. The results of this study indicate that the implementation of the recruitment of educators at SMA Nurul Amal has been going well. This can be seen from (1) Planning for recruitment of educators (2) Dissemination of announcements for recruitment of educators (3) Acceptance of applications for prospective educators. (4) Selection: a) applicant selection system holding interviews and filling out forms, b) applicant selection process, the committee screens applicants such as looking at educational background, experience, and desired position. c) Applicant selection method, the school conducts the interview method. The supporting factors for the implementation of the recruitment of educators at SMA Nurul Amal Palembang are: a) facilities, b) cooperation between teams, c) human resources. Factors inhibiting the implementation of the recruitment of educators at SMA Nurul Amal Palembang, namely: lack of coordination.